Da autonomia à independência : a Catalunha e o impacto das novas demandas nacionalistas na política do CDC - Cappelatti, Mariana Dexheimer (2018)
The main objective of this dissertation is to understand how the main transformations that boosted the great independentist turn of the Catalan nationalism took place in the inauguration speeches of the leaders from the key party CDC, while presidential candidates of the Generalitat, the Catalan government. With the rise of new popular demands for independence as of 2010, and after the (illegal) referendum a few years later, that won with an imperative victory of the "yes" to independence, there was a sharp shift on the emphasis of the party: from moderate and autonomist, CDC began to treat the independence of Catalonia as the main objective of its governments. With the inaugurations speeches from 1980 and 1999 of Jordi Pujol, from 2010 and 2012 of Artur Mas, and the one from 2016 of Carles Puigdemont, the research intends to find the most important points that constituted the character of the transformation, as well as the role of ethnic, civic and economic nationalism in these changes. With the use of documental analysis, the dissertation is going to address as preliminary analisys the historical, social and economic contexto f the speeches, the profiles of the authors, in addition to key concepts and the internal logic of each of the speeches, in order to reach a more concise final analysis of the central problem of the work. It was comprehended that even though it is quite difficult to estabilish a cause-and-effect-relationship, it was noted the significative role of the consequences of the economic crisis of 2008 and the changes on the Statute of Autonomy of 2006 in the essence of the Catalan nationalism, that ended up inferring in a new dynamic bewteen civil society and political elites, generating the transformations inside CDC, alterating their main policies and strengthening their political use of nationalism.